EFFECT OF ADDITION OF SODIUM BENZOATES IN GREEN SUGAR CANE JUICE (Saccharum Officinarum L.) ON THE APPLICATION PULSED ELECTRIC FIELD (PEF) CONTINUOUS SYSTEM - Dina Wahyu Indriani; Sumardi Hadi Sumarlan; Nurul Dwi Hidayani; Arie Febrianto Mulyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
Non-thermal pasteurization process using Pulsed Electric Field (PEF) today has been used particularly in processed food products are easily contaminated. One cause contamination of processed products is the high number of microbes in the product example is a green cane juice (Saccarum officinarum) and thus require proper handling process is to conduct non-thermal pasteurization using Pulsed Electric Field (PEF) continuous system. This study aims to reduce the total number of microbes and it maintains the physical and chemical qualities of green cane juice. In this study also added sodium benzoate which serves to inhibit microbial growth and increase shelf life of cane juice. This study uses a Randomized Complete Block design (RCB) with 2 factors that PEF continuous voltage (20, 30 and 30 kV) and the addition of sodium benzoate concentrations (200, 400, and 600 ppm) with 2 replications. Best research results at a voltage of 40 kV and a concentration of 600 ppm sodium benzoate. In this combination had a mean number of total microbes of 4.15 x 106 cfu / ml, TPT at 12.9 ° brix, total cave of 11.61%, a viscosity of 5.5 cp, the color on the brightness value (L *) of 24.1, redness (a *) of 7.1 and yellowness (b *) of 7. The color of the green cane juice controls had no significant difference it showed that PEF continuous system is able to maintain the color of the green cane juice.Keywords: Continuous; Green Cane Juice; Pulsed Electric Field; Sodium Benzoate